PENDIDIKAN KESEHATAN TENTANG MAKANAN PENDAMPING ASI DINI TERHADAP TUMBUH KEMBANG BAYI DI POSYANDU DESA BANGSALAN TERAS BOYOLALI - Erna Wati; Arista Apriani; Erinda Nur Pratiwi; Atiek Murharyati (LPPM Universitas Pekalongan, 2022)
Complementary foods are complementary foods given to infants after the age of 6 months. If complementary feeding is given too early (before the age of 6 months) it will reduce the consumption of breast milk and the baby can experience digestive disorders. On the other hand, if complementary foods are given too late, the baby will be malnourished, if it occurs for a long time. Early childhood babies are very susceptible to bacteria that cause diarrhea, especially in an environment that lacks hygiene and poor sanitation. Looking at the results , there needs to be more attention from Integrated Healthcare Center cadres in improving services, especially regarding the provision of appropriate complementary feeding.Keywords: Complementary foods, breast milk, Integrated Healthcare Center, breastfeeding